Malignant melanoma arising within ovarian mature cystic teratoma (Journal of Pathology of Nepal, 2019)
Mature cystic teratomas are frequently encountered neoplasms of the ovary that comprise of tissues derived from all three germ layers. They are benign neoplasms with malignant transformation noted rarely in around 0.1 to 3% cases. Among the various transformations, malignant melanoma is one of the least commonly encountered. Here, we report a case of 41 years old female with malignant melanoma arising within mature cystic teratoma.